2021
DOI: 10.1073/pnas.2112605118
|View full text |Cite
|
Sign up to set email alerts
|

Within and between classroom transmission patterns of seasonal influenza among primary school students in Matsumoto city, Japan

Abstract: Schools play a central role in the transmission of many respiratory infections. Heterogeneous social contact patterns associated with the social structures of schools (i.e., classes/grades) are likely to influence the within-school transmission dynamics, but data-driven evidence on fine-scale transmission patterns between students has been limited. Using a mathematical model, we analyzed a large-scale dataset of seasonal influenza outbreaks in Matsumoto city, Japan, to infer social interactions within and betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In this study, the vaccine status of the individual cases was not associated with changes in the risk of secondary cases, suggesting that while vaccination is protective against infection, it might not necessarily prevent onwards transmission if breakthrough infection happens. A study conducted among children in Matsumoto city, Japan also reported an association between vaccination and reduction in susceptibility, with vaccination having a more limited association with onwards transmission 43 . Recently published studied also reported the low degree of indirect protection by childhood vaccination supporting the results of the current study 44 .…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the vaccine status of the individual cases was not associated with changes in the risk of secondary cases, suggesting that while vaccination is protective against infection, it might not necessarily prevent onwards transmission if breakthrough infection happens. A study conducted among children in Matsumoto city, Japan also reported an association between vaccination and reduction in susceptibility, with vaccination having a more limited association with onwards transmission 43 . Recently published studied also reported the low degree of indirect protection by childhood vaccination supporting the results of the current study 44 .…”
Section: Discussionmentioning
confidence: 94%
“…Other countries were observed to have different levels of school closure during the study period compared with Switzerland and so the “ideal” amount of closure remains to be determined. We note that school closures are a primary measure for disease control but other measures such as masked students or vaccinated students which seek to reduce within-class disease risk may be a better option later in the outbreak [Endo et al, 2021]. We remain cognisant that the purpose of school is not just educational and it is important to investigate the impact of this as the knock-on effects to children’s health of remote learning are expected to be a topic of interest for years to come.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 case data is provided by the Swiss public health authority (Bundesamt für Gesundheit) and includes case counts by date reported stratified by age group. We asked for cases given by the same age groups we considered in our Zurich analysis as this roughly divides the population into those of compulsory education age (0-14 year olds are required to be in school when school is open), higher education and young workers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), parents (25-44), middle-aged workers (45-65), retirees (66-79), and the elderly (80+). Our age group thresholds include the commonly used cut-off of 65 years of age considered in epidemiology, when health is expected to change.…”
Section: Datamentioning
confidence: 99%
“…In our study, a total of four models incorporating different combinations of (1) the depletion effect (with and without) and (2) scaling factors (global and region-specific) were considered. To determine which model best describes the observed mpox importation patterns, we compared the four candidate models and selected the best model by the Laplace-approximated model evidence (LAME) 46,47 , which is closely related to the Bayesian Information Criterion (BIC) but does not rely on the assumption that data are independent and identically distributed (i.i.d). Given the non-independent nature of our data where the occurrence of importation events in a country would affect the importation hazard in other countries, we employed the LAME which is defined as: where 𝜙(𝜃 0 ) is the prior density of the maximum a posteriori estimate, for which we used an improper flat prior (𝜙(𝜃) = 1 ).…”
Section: Supplementary Materials: Dynamic Landscape Of Mpox Importati...mentioning
confidence: 99%